LaF3 nanolayer surface modified spinel LiNi0.5Mn1.5O4 cathode material for advanced lithium-ion batteries. Issue 4 (March 2018) - Li, Yaping; Zhang, Qian; Xu, Tinghua; Wang, Dandan; Pan, Du; Zhao, Huiling; Bai, Ying
Abstract: As an attractive high power-density cathode material for lithium-ion batteries, spinel-structured LiNi0.5 Mn1.5 O4 (LNMO) so far still suffers fast capacity decay during repeated cycling due to transition metal (TM) dissolution and structure degradation. In this work, a thin nanolayer of LaF3 is applied to modify the surface of LNMO. Electrochemical and thermal tests indicate that 4 wt% LaF3 surface modification could greatly improve the electrode performances in terms of cycling stability and rate capability as well as thermal stability of LNMO compared with the pristine electrode, without influencing the crystallographic structure of bulk material. Further analysis for understanding the intrinsic mechanism reveals that the growth of solid electrolyte interface (SEI) film could be effectively suppressed by the surface LaF3 nanolayer, which meanwhile stabilizes the bulk structure through retarding continuous TM dissolution from intensive chemical aging measurements at elevated temperature. This work, theoretically and technically, provides a promising alternative approach for enhancing electrochemical performances of high voltage LNMO cathode material.